The Initiation of Green Libraries: The Case of STIE Perbanas Surabaya's Library - Munawaroh, Munawaroh; Bestari, Melati Purba (UI Scholars Hub, 2018)
Why study green libraries? We know that as of 2007, paper and paperboard makes up 33% of total municipal solid waste recycling. This suggests that libraries contribute to this figure as libraries’ collections and operational materials are made up of paper. Through a literature review and a case study, this paper will examine how to create a management system for a green library. This system is implemented as a Green library at the Kasetsart University Library. This paper will apply its results to the STIE Perbanas Surabaya Library as the next site for the implementation of a green library. In order for library services to survive, libraries must change their management to address the issue of global warming, create interest and delight in libraries on the part of borrowers and enable emerging librarians to foster an entrepreneurial spirit.